Facilitating engagement of universal school-based digital mental health solutions through user experience: A qualitative exploration - Badawi, Erfan; Coursaris, Constantinos K.; Sénécal, Sylvain; Léger, Pierre-Majorique (Frontiers in Digital Health, 2023)
Digital mental health intervention (DMHI) programs offered in schools present a crucial and inexpensive investment, also a readily-accessible and flexible means for educating, empowering, and supporting adolescents in maintaining a balanced mental health during uncertain and stressful times such as COVID-19 pandemic. Recent studies indicate that for DMHI programs to be effective in improving students’ mental well-being and in preventing from their mental health complications, user engagement is key. This study focuses on identifying the factors pertaining to user experience of digital solutions that can facilitate user engagement with DMHI programs that schools deliver universally to their students, regardless of their mental health conditions. To identify said factors, we sought to gain a deeper understanding of perceptions, opinions, and preferences of the actual end-users (i.e., the adolescents) regarding their experiences with both digital and non-digital mental health resources and thus investigated what constitute the primary user expectations (or a digital solution’s must-haves) and the additional user desires (or a solution’s nice-to-haves) that contribute to engagement with universal school-based DMHI programs. Specifically, through conducting interviews with adolescents who had either a higher-than-average or a lower-than-average engagement with universal DMHI programs of a specific school-based digital mental health solution, also adolescents who had voluntarily used non-digital or non-school-based digital mental health resources for purposes other than treatment, the reasons that could lead the adolescents to better engage with school-based DMHI programs, as well as the shortcomings that could prevent that from happening were uncovered. By performing a thematic analysis, the most important (or primary) and the additionally desirable (or secondary) factors that that could lead to a higher engagement level for school-based DMHI programs were identified. Lastly, using the gathered evidence from our interviews, specific recommendations are proposed that could help in targeting each identified engagement factor and in increasing the likelihood that school-based DMHI programs achieve their desired outcome for high school students.